Perception of entrepreneurship as a sustainable career option by women in rural areas - Dzomonda, O.; Masocha, R. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The emancipation of women is an emerging area which is at the heart of many agendas of various nations worldwide. An entrepreneurship career can offer momentous opportunities to women in rural areas and enable them to realise financial independence as well as benefit the economy by contributing towards job creation. The purpose of this paper is to investigate how women in rural areas perceive entrepreneurship as a sustainable career option. The study was based on a quantitative research design. The survey method was used as a data collection method. Using this method, self-administered questionnaires were used as the primary data collection tool. These questionnaires were hand delivered to the participants by the researcher. The convenience and snowball sampling methods were used to obtain the participants. The population consisted of women in Ga-Sekopo rural area. 73 women participated in the survey. Data analysis included descriptive statistics and T tests. The Cronbach’s alpha was used as a measure of reliability. The findings showed that women in rural areas have negative perceptions about the entrepreneurship career. This was based on the perception that the career is highly risk, with no clear benefits and that they have doubts in obtaining support from the government. Results from T tests showed that there is a significant difference on the perception of entrepreneurship by women in rural areas based on their level of education. The study concluded by proposing that the government should design a consortium of programmes aimed at raising entrepreneurship awareness among women in rural areas.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Career; Entrepreneurship; Women; Entrepreneurship -- South Africa; Rural women -- South Africa